Proposed new interior design for the Red Warrior Cafe, Kota Bharu, Kelantan / Mohamad Zainuddin Mohamad Maidin - Mohamad Maidin, Mohamad Zainuddin (Faculty of Architecture, Planning & Surveying, 2010)
A final year Student of Interior Design is required to prepare a final year project. All the design must be related to the project that have been choose. Before doing the design, main aspect must be considered to get the Information. So that, we must do a research, case study, design schematic and the planning to make sure that dient will give the good feedback with our design. Proposed new interior design of The Red Wanrior Cafe is a one of the direct advantages to Kelantan's fans club. It is because, followed the objective and the issues and a space planning was come out with the design concept and the images. So, to implement the design into the space is a complicated way because it has the stages we must follow. The planning that we have been created and the ideas that we want to implement into the space must be related to the concept and the images. With the concept The Glorious of Red1 and modern image will implement into the space. So, conclusion is, the good design is how we implement the concept and the images into the design cafe, followed by the development of ideas.